THE ART OF SPEECH: THE POWER OF WORDS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article analyzes the essence of speech, its significance in social life, and the specific features of the art of oratory. Based on the works of ancient orators, particularly Cicero, as well as modern researchers (Golden, Gehring, James, Smith, and others), the structure, style, and factors of expressiveness in speech are revealed. In addition, the paper examines interactive forms of lecture speech in the educational process, their effectiveness, and their role in establishing communication with the audience. The research results contribute to a deeper understanding of the role of speech in social, pedagogical, and cultural processes.